Occurrence of self‐perceived medical errors and its related influencing factors among emergency department nurses. Issue 1 (17th January 2022) - Wang, Jing; Mu, Ketao; Gong, Yanhong; Wu, Jianxiong; Chen, Zhenyuan; Jiang, Nan; Zhang, Guopeng; Lv, Chuanzhu; Yin, Xiaoxv
Abstract: Aims and objectives: To determine the prevalence and the associated factors of self‐perceived medical errors among Chinese emergency department nurses. Background: The emergency department is a place with a high incidence of medical errors. Studies about the occurrence and related influencing factors of medical errors among emergency nurses in China are very insufficient. Design: A nationwide cross‐sectional study. Methods: A nationwide cross‐sectional study was conducted from July 2018–August 2018. A total of 17, 582 emergency department nurses from 31 provinces across China were eventually included in the analysis. Logistic regression is applied to examine the association of the independent variables with the perceived medical errors. The reporting of this study was compliant with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist for cross‐sectional studies. Results: Of 17, 582 participating nurses, 4445 (25.28%) reported self‐perceived medical errors in the past 3 months. Nurses who were serving as nurses‐in‐charge; who reported fair or bad physical health; who reported staff shortage; who were exposed to more verbal abuse at work; who experienced effort–reward imbalance; who reported more over‐commitment; or who had depressive symptoms were more likely to report medical errors. Older age and female gender were protective factors. Conclusions: In this study, a quarter of the emergency nurses reported that they had made medical errors in the past 3 months. Self‐perceived medical errors are associated with multiple domains of work‐related factors and personal distress. Feasible measures should be taken to reduce nurses' workload, improve their working environment, monitor and minimise the occurrence of medical errors among emergency department nurses. Relevance to clinical practice: Emergency nurses, who are the most frequently in contact with patients, play an important role in identifying risk factors and preventing medical errors. Identifying risk factors that may lead to medical errors in the medical environment from both internal and external aspects will help nursing practitioners, hospital administrators and policy makers to take timely preventive measures to reduce the occurrence of medical errors and reduce harm to patients.